Development of Concrete Media in Reading and Writing Literacy of Grade 1 Elementary School Students in Region III, Batalaiworu District (Lembaga Pengembangan Kinerja Dosen, 2025)
The aim of this research is to develop concrete media for literacy learning in reading and writing. The research method used is research and development methodology that adapts the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study are first-grade elementary school students. The research instruments used in this study include a product assessment scale by material and media experts, as well as assessment questionnaires by teachers and student responses. The results of this research are concrete media for reading and writing literacy learning. The feasibility test results according to material experts received a score of 83% with good criteria, and a score of 91% with very feasible criteria from media experts. Additionally, the developed concrete media received good ratings and positive responses from first-grade students.